DYRK1A roles in human neural progenitors - Courraud, Jeremie; Quartier, Angélique; Drouot, Nathalie; Zapata-Bodalo, Irene; Gilet, Johan; Benchoua, Alexandra; Mandel, Jean-Louis; Piton, Amélie (Frontiers in Neuroscience, 2025)
IntroductionMutations in dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) represent one of the most prevalent monogenic causes of neurodevelopmental disorders (NDDs), often associated with intellectual developmental disorder and autism spectrum disorder. DYRK1A encodes a dual-specificity kinase (tyrosine and serine/threonine) that plays a key role in various cellular processes and is a critical regulator of nervous system development.MethodsFor the first time, we have characterized the DYRK1A interactome and study the consequences of DYRK1A depletion in human neural stem cells (hNSCs).ResultsWe identified 35 protein partners of DYRK1A involved in essential pathways such as cell cycle regulation and DNA repair. Notably, five of these interactors are components of the anaphase-promoting complex (APC), and one is an additional ubiquitin ligase, RNF114 (also known as ZNF313), which is known to target p21. Many of these identified partners are also linked to other human NDDs, and several others (e.g., DCAF7 and GSPT1) may represent novel candidate genes for NDDs. DYRK1A knockdown (KD) in hNSCs using siRNA revealed changes in the expression of genes encoding proteins involved in extracellular matrix composition and calcium binding (e.g., collagens, TGFβ2 and UNC13A). While the majority of genes were downregulated following DYRK1A depletion, we observed an upregulation of early growth factors (EGR1 and EGR3), as well as E2F2 and its downstream targets. In addition, DYRK1A-KD led to a reduction in p21 protein levels, despite an increase in the expression of a minor transcript variant for this gene, and a decrease in ERK pathway activation.DiscussionTogether, the DYRK1A interactome in hNSCs and the gene expression changes induced by its depletion highlight the significant role of DYRK1A in regulating hNSC proliferation. Although the effects on various growth signaling pathways may appear contradictory, the overall impact is a marked reduction in hNSC proliferation. This research underscores the pivotal role of DYRK1A in neurodevelopment and identifies, among DYRK1A’s protein partners and differentially expressed genes, potential novel candidate genes for NDDs and promising therapeutic targets for DYRK1A syndrome.